Lactobacillus plantarum MYS6 Ameliorates Fumonisin B1-Induced Hepatorenal Damage in Broilers - Deepthi, B. V.; Somashekaraiah, Rakesh; Poornachandra Rao, K.; Deepa, N.; Dharanesha, N. K.; Girish, K. S.; Sreenivasa, M. Y. (Frontiers in Microbiology, 2017)
Fumonisin B1 (FB1), a mycotoxin produced by Fusarium species is a predominant Group 2B carcinogen occurring in maize and maize-based poultry feeds. It is shown to be nephrotoxic, hepatotoxic, neurotoxic and immunosuppressing in animals. In this study, we report the ameliorating effects of a probiotic strain, Lactobacillus plantarum MYS6 on FB1-induced toxicity and oxidative damage in broilers. A 6-week dietary experiment consisting of 48 broilers was performed in 6 treatment groups. Probiotic treatment (109 cells/mL) involved pre-colonization of broilers with L. plantarum MYS6 while co-administration treatment involved supplementation of probiotic and FB1-contaminated diet (200 mg/Kg feed) simultaneously. At the end of the treatment period, growth performance, hematology, serum biochemistry, and markers of oxidative stress in serum and tissue homogenates were evaluated in all the broilers. The histopathological changes in hepatic and renal tissues were further studied. The results demonstrated that administration of L. plantarum MYS6 efficiently improved the feed intake, body weight and feed conversion ratio in broilers. It mitigated the altered levels of hematological indices such as complete blood count, hemoglobin, and hematocrit. Serum parameters such as serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, creatinine, cholesterol, triglycerides and albumin were significantly restored after administering the probiotic in FB1-intoxicated broilers. Additionally, L. plantarum MYS6 alleviated the levels of oxidative stress markers in serum and tissue homogenate of liver. The histopathological data of liver and kidney further substantiated the overall protection offered by L. plantarum MYS6 against FB1-induced cellular toxicity and organ damage in broilers. Our results indicated that co-administration of probiotic along with the toxin had better effect in detoxification compared to its pre-colonization in broilers. Collectively, our study signifies the protective role of Lactobacillus plantarum MYS6 in ameliorating the FB1-induced toxicity in the vital organs and subsequent oxidative stress in broilers. The probiotic L. plantarum MYS6 could further be formulated into a functional feed owing to its anti-fumonisin and anti-hepatorenal-damage attributes.